Community perception of abandoned residential buildings in Klang, Selangor / Nurul Izzatie Izmahanis Jaron - Jaron, Nurul Izzatie Izmahanis (Universiti Teknologi MARA (UiTM), 2025)
In Malaysia, the issue of abandoned residential buildings has grown to be a significant urban concern, especially in rapidly developing areas unfinished construction, deteriorating structures, and a lack of maintenance are common characteristics of abandoned buildings, which lead to many social, economic, and environmental problems. Abandoned buildings, which are frequently connected with urban decay and neglect, represent substantial threats to the well-being and social cohesion of surrounding communities. In addition, deterioration, danger, and criminal activity are among the negative imagery that is commonly associated with these structures. Therefore, the perception and general well-being of those who live close by are greatly impacted by abandoned residential buildings.